Anxiety, depression and stress during the COVID-19 pandemic: Results from a cross-sectional survey - Turna, Jasmine; Zhang, Jasmine; Lamberti, Nina; Patterson, Beth; Simpson, William; Francisco, Ana Paula; Bergmann, Carolina Goldman; Ameringen, Michael Van (Journal of psychiatric research, 2021)
Multiple survey studies have demonstrated a mental health (MH) burden of COVID-19 globally. However, few studies have examined relevant risk factors for pandemic-related MH issues. A link to an online survey was posted from April 8th - June 11th, 2020 which included questions regarding COVID-19 experience, perceived impact of the pandemic on life domains (e.g., social communication, finances), behavioural alterations (e.g., online activities, substance use), and MH treatment history. Current psychiatric symptom severity and impairment were evaluated using the Generalized Anxiety Disorder-7, Patient Health Questionnaire-9, and the Perceived Stress Scale. Overall, 632 individuals (82% female, mean age:42.04 ± 16.56) in Canada and the United States completed the survey. While few reported contracting COVID-19 (0.5%), the impact of the pandemic was evident, with a vast majority reporting anxiety around COVID-19 infecting loved ones (88%). Almost half (43%) reported previous MH treatment and 31% met criteria for GAD, 29% for MDD and 63% reported significantly high levels of stress. Female sex, younger age and past MH treatment emerged as significant predictors of these issues(p < .01). Age-related differences in the impact of COVID-19 on life domains, substance use, and online activity were also noted. The findings from the current sample add to the growing literature suggesting negative effects of COVID-19 on MH, while highlighting specific risk factors. Age may be an important factor in predicting MH during this pandemic.